The most bothersome symptom of vaginal atrophy: Evidence from the observational AGATA study. (February 2018) - Palma, Federica; Xholli, Anjeza; Cagnacci, Angelo; ,
Highlights: The prevalence of the most bothersome symptom (MBS) of vaginal atrophy was investigated in a multicenter national study. Among all symptoms, vaginal dryness, was the most frequently reported MBS (54.4% of women). The identification of the MBS may help to define a more appropriate management of vaginal atrophy. Abstract: Objectives: Vaginal atrophy (VA) is a chronic medical condition. It is managed unsatisfactorily, despite its high prevalence and negative impact on female quality of life. In order to meet their needs, it would be useful to know what women perceive to be the most bothersome symptom (MBS) of VA. Study design: Cross-sectional, multicenter study of 913 postmenopausal women consulting 22 gynecological outpatient services. Main outcome measures: Prevalence of the MBS perceived by postmenopausal women of different age and vaginal condition. Results: Vaginal dryness was the most prevalent MBS (54.4%), followed by dyspareunia (17.6%), itching (7.8%), dysuria (5.9%) and burning (2.0%). The prevalence of vaginal dryness as the MBS increased with years since menopause, while that of itching, dysuria and burning remained approximately constant over time. The prevalence of dyspareunia as the MBS was 26.2% in the first 6 years after menopause and declined thereafter, to 8.8%. Conclusions: Among all postmenopausal women vaginal dryness per se, independent of dyspareunia, is the most commonly reported MBS. In each woman, the identification of the MBS may help to define more appropriate VA management.